The price of inattention: Evidence from the Swedish housing market - Luca Repetto; Alex Solis (Uppsala University, Department of Economics, 2017)
Do behavioral biases a affect prices in a high-stake market? We study the role of left digit bias in the purchase of an apartment, one of the most important assets in a household's portfolio. Left-digit bias is the inability to fully process digits after the first, perceiving prices just below a round number (such as 3.99) as cheaper than their round counterpart (4). We start by documenting that apartments listed at just-below asking prices are sold at a 3-5% higher final price after an auction. This effect appears not to be driven by i) differences in observable characteristics; ii) differences in real estate agents' behavior; or iii) institutional characteristics of the market. We show that apartments using just-below prices attract more bidders and bids, leading to higher competition and to a higher final price. Our results suggest that inattentive buyers might be losing roughly half a year of disposable income.
urn:nbn:se:uu:diva-331189
Keywords: R31; D44; D83; C78; 330; Housing market; auctions; inattention; first-digit bias